Vestígios arqueológicos no alto curso da bacia do Rio da Várzea e região norte do Rio Grande do Sul - Kolling, Lieli Coelho (2024)
Despite the considerable increase in the amount of paleontological and, mainly, archaeological research in the state of Rio Grande do Sul in recent years, the northern region of the state still lacks research capable of explaining the details of the processes of occupation of the territory throughout Ancient History. . In this sense, the present work seeks to present the paleontological and archaeological potential of the region, specifically the territories that today are part of the municipalities of Novo Barreiro, Chapada, Rondinha, Coqueiros do Sul, Carazinho and Braga in the state of Rio Grande do Sul, circumscribing the upper basin of the Várzea River. Initially, it discusses the period of the Pleistocene fauna of extinct giant mammals, the megafauna, the conceptualization of paleotoca and the occurrences recorded by the Paleotocas Project, a pioneer and reference in the area, as well as the paleontological potential of the northern region. Subsequently, the Ancient History of Rio Grande do Sul and the archaeological potential in the upper reaches of the Rio da Várzea basin are presented in general. The region in question is historically and geographically characterized, presenting material remains as archaeological potential. The artifacts studied belong to two types of collections, private collections, made up of objects collected by residents of the municipalities of Novo Barreiro and Rondinha, and institutional collections, belonging to the archaeological collections of the Municipal History Museum of Chapada and the Olívio Otto Museum, located in municipality of Carazinho. This last collection, due to the volume and characteristics of the artifacts, as well as the approximate origin of its location - Xadrez District in the 1970s, at the time belonging to Carazinho and currently in the municipality of Coqueiros do Sul - is considered with greater emphasis. In addition to these specimens, we also sought to present the collections from the Braga Region, currently the municipality of Braga. These are, therefore, different relationships and functions with the remains of Ancient History in this geographical area. The first comprise interaction with the landscape, access and direct intervention by communities; the second are found in residents' homes, originating from collections in planting areas and river banks; while the third is under the custody of an institution, making up its technical reserve. In short, the great archaeological potential of the northern region of Rio Grande do Sul is considered, in which systematic research and excavation projects would help to clarify the processes of occupation and settlement, including the presence of hunter-gatherers, ceramic groups and, more recently, from the interaction of distinct ethnic groups, arriving since the 19th century, with such remnants.